2014
DOI: 10.1371/journal.pone.0098528
|View full text |Cite
|
Sign up to set email alerts
|

HER2 Status in Colorectal Cancer: Its Clinical Significance and the Relationship between HER2 Gene Amplification and Expression

Abstract: This study aimed at determining the incidence and clinical implications of HER2 status in primary colorectal cancer (CRC). HER2 status was investigated in two retrospective cohorts of 365 consecutive CRC patients (cohort 1) and 174 advanced CRC patients with synchronous or metachronous distant metastasis (cohort 2). HER2 status was determined by performing dual-color silver in-situ hybridization (SISH), mRNA in-situ hybridization (ISH), and immunohistochemistry (IHC). The incidence of HER2 protein overexpressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
107
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(133 citation statements)
references
References 39 publications
4
107
2
Order By: Relevance
“…The rate of HER2/ neu amplification was lower in our study compared to published literature but differential amplification was observed in primary colon tumors and lung metastases (1.8% vs 4%). Previous studies have quoted a 5-9% incidence of HER2/neu amplification in CRC 26,27 and HER2/neu amplification was shown to be concordant in only 5% of the primary and metastatic lesions. 27 In a study by Ramanathan et al, HER2/neu-positive patients with advanced colorectal cancer were treated with trastuzumab (Herceptin Ò and irinotecan).…”
Section: Discussionmentioning
confidence: 87%
“…The rate of HER2/ neu amplification was lower in our study compared to published literature but differential amplification was observed in primary colon tumors and lung metastases (1.8% vs 4%). Previous studies have quoted a 5-9% incidence of HER2/neu amplification in CRC 26,27 and HER2/neu amplification was shown to be concordant in only 5% of the primary and metastatic lesions. 27 In a study by Ramanathan et al, HER2/neu-positive patients with advanced colorectal cancer were treated with trastuzumab (Herceptin Ò and irinotecan).…”
Section: Discussionmentioning
confidence: 87%
“…[6][7][8][9][12][13][14][15][16][17][18][19][20] The present study is unique because the only study with an equally large sample size, albeit without clinical validation, reported much lower rates of both ERBB2 expression (2.7%) and positive amplification (1.6%). 8 This difference very likely resides in the fact that while our findings have been obtained on a primarily metastatic population, Heppner et al 8 tested only primary tumors using a different staining antibody (SP3) and a different in situ hybridization method (CISH), and employed gastric cancer criteria to test and score the samples.…”
Section: Discussionmentioning
confidence: 94%
“…1,2 Overexpression of ERBB2 is an established therapeutic target in breast and gastric cancers and is successfully exploited in the clinic using a variety of anti-ERBB2 agents, leading to remarkable outcome improvements. 3,4 Although the comprehensive molecular characterization of human colorectal cancer has identified ERBB2 amplification as a potential therapeutic target 5 and ERBB2 overexpression has been controversially linked to prognosis, [6][7][8][9] the clinical significance of ERBB2 alterations remains elusive. Recently, we and others have found that activation of ERBB2 signaling causes resistance to anti-EGFR therapy in a fraction of metastatic colorectal patients, wild type for RAS codons 12-13.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Activation of her2 plays a key role in cell proliferation, cell differentiation, inhibition of apoptosis, and tumour progression 100 . Several trials tried to assess the overexpression of her2 in the gastrointestinal tract, with results ranging from 0%-83%, the wide range being thought to be a result of differences in methods and reagents used for the tests 101 .…”
Section: Evidence Summarymentioning
confidence: 99%